Marketing Strategy For The Indonesian Launch of Japan’s Small Electric Vehicle: An Exploratory Study - Dewi, Cicilia Erni Cynthia; Suwartini, Suwartini; Hidayati, Aprihatiningrum (Business Review and Case Studies, 2025)
Background: The electric vehicle (EV) market in Indonesia has garnered significant attention, particularly in the city car segment that is dominated by Chinese brands. Government support and growing demand for eco-friendly alternatives have paved the way for the introduction of electric vehicles in Indonesia. Purpose: This study aims to formulate a relevant marketing strategy for PT XYZ’s upcoming launch of a Japanese city car electric vehicle in Indonesia scheduled for 2025-2026. Design/methodology/approach: This study employs a qualitative, exploratory approach, utilizing in-depth interviews with PT XYZ’s management and Focus Group Discussions (FGDs) with city car electric vehicle users. Data analysis was conducted using coding and categorization methods. Findings/results: The findings reveal a strong market potential for city car electric vehicles, especially in urban areas. Key drivers include government incentives and the desire to lower operational costs. The proposed marketing strategy integrates the STP model (Segmentation, Targeting, and Positioning) and the 4P framework (Product, Price, Place, Promotion), focusing on modern urban consumers, with product differentiation through design, premium features, and competitive pricing. Conclusion: PT XYZ’s brand image as a trusted Japanese manufacturer plays a critical role in differentiating its product from its competitors, particularly Chinese brands. This strategy fosters consumer trust, and positions PT XYZ as a viable player in the Indonesian electric vehicle market. Originality/value (State of the art): This study contributes to the literature on electric vehicle marketing strategies, providing valuable insights for PT XYZ in navigating the competitive landscape and enhancing its market entry strategy for city car electric vehicles in Indonesia. Keywords: marketing strategy, electric vehicle, city car, STP, 4P, competitive advantage